2023
DOI: 10.1002/aisy.202200265
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer Bending Actuators Based on Semicrystalline Polyurethanes with Large Thermal‐Expansion Coefficients

Abstract: Thermoresponsive polymer‐based bilayer bending actuators rely on the dissimilar thermal expansion of the polymers that form the two layers. To maximize the heat‐induced change in curvature, the thermal expansion shall be large in one and small in the other material. Semicrystalline polymers display a large nonlinear thermal expansion across their melting transition, but as their mechanical integrity is lost upon melting, they cannot readily be used in bilayer actuators. To overcome this limitation, segmented p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The PEG-PU employed in this study was designed based on a recently reported approach to create polymers displaying large coefficients of linear thermal expansion (CLTE) in a narrow temperature range. [44,45] The polyethylene glycol (PEG) blocks form semicrystalline domains, while the hard blocks containing the urethane groups act as physical crosslinks. The polymer softens and a large nonlinear thermal expansion is observed upon heating and melting of the PEG crystals, but the material liquefies only at a much higher temperature, where the urethane hard phase dissociates.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The PEG-PU employed in this study was designed based on a recently reported approach to create polymers displaying large coefficients of linear thermal expansion (CLTE) in a narrow temperature range. [44,45] The polyethylene glycol (PEG) blocks form semicrystalline domains, while the hard blocks containing the urethane groups act as physical crosslinks. The polymer softens and a large nonlinear thermal expansion is observed upon heating and melting of the PEG crystals, but the material liquefies only at a much higher temperature, where the urethane hard phase dissociates.…”
Section: Resultsmentioning
confidence: 99%
“…The specific material utilized here was synthesized according to a recently reported protocol. [ 45 ] Based on the reported structure‐property relations of PEG‐PUs, and with the goal to optimize thermal expansion, the PEG‐PU employed here was synthesized by the reaction of hydroxyl‐terminated PEG with a number‐average molecular weight ( M n ) of 10 kg mol −1 , 7 wt.% 1,4‐butanediol (BDO) as chain extender, and 1,6‐hexane diisocyanate. The resulting PEG‐PU had an M n of 41 kg mol −1 , as determined by size‐exclusion chromatography.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations